Addressing Needs and Challenges of Life and Career-skills in English Learning Material: A Systematic Review - Abid Hakiki; Sri Sumarni; Darmahusni Darmahusni (Universitas Muhammadiyah Semarang, 2023)
Current issues in education have led English learning materials to incorporate 21st century skills, including life and career-skill. This study aimed to investigate the availability of life and career skills in English learning material and to address needs and challenges of the incorporation of life and career skills. A systematic review was employed to analyse studies that presented the incorporation of life and career skills in English learning material. To ensure the selected articles are thoroughly analysed, PRISMA (referred Reporting Items for Systematic review and Meta-Analyses) 2020 guidelines were utilized. A total of 15 peer-reviewed journal articles published between 2013 to 2023 were retrieved from two databases: Google Scholar and ERIC. The findings showed that life and career skills have been incorporated but somehow insufficient and need to be developed. In addition, the findings revealed that life and career skills in English learning material was highly needed because of these reasons: 1) the lack of life skill-based learning material; 2) the gap between the skills possessed and skills required; 3) the students need to compete globally; 4) the students need to train their critical thinking, collaboration and communication skill; 5) the needs of teachers’ role. Meanwhile, the findings revealed the challenges such as: 1) the limitation of time and resources 2) The difficulty to integrate all skills in the learning material; 3) The material is somehow inadequate and insufficient; 4) The English material cannot be applied to wider area; 5) Some material are difficult to understand. In conclusion, the findings provide the important insight into developing life and career-skills English learning material in Indonesia. The challenges found can be used to overcome the problem while developing English learning material.